Performance of behavioral assays: the Rat Grimace Scale, burrowing activity and a composite behavior score to identify visceral pain in an acute and chronic colitis model. (March 2019) - Leung, Vivian S.Y.; Benoit-Biancamano, Marie-Odile; Pang, Daniel S.J.
Abstract: Introduction: The Rat Grimace Scale (RGS), a facial expression scale, quantifies the affective component of pain in rats. The RGS was developed to identify acute and inflammatory pain, and applicability in acute and chronic visceral pain is unknown. The dextran sulfate sodium (DSS) colitis model is commonly used in rats, but pain is rarely assessed, instead, disease progression is monitored with the Disease Activity Index (DAI; assessing fecal blood, stool consistency, and weight loss). Objectives: The aim of this study was to assess whether the RGS and 2 additional behavioral tools (composite behavior score [CBS] and burrowing) could identify pain in an acute and chronic DSS colitis model. Methods: Male and female Sprague-Dawley rats were block randomized to (1) acute colitis (4 days DSS in drinking water); (2) chronic colitis (4 days DSS, 7 days water, and 3 days DSS); or (3) control (14 days water). Disease Activity Index, RGS, CBS, and burrowing assessments were performed daily. Results: Rat Grimace Scale scores increased as DAI scores increased during both acute and chronic phases. Burrowing only decreased during the acute phase. By contrast, CBS scores did not increase significantly during either colitis phase. Conclusions: These data show that the RGS and burrowing did not decrease in a sustained manner during chronic phase visceral pain, and that variables assessed in the DAI are indicative of pain. This suggests that the RGS can be applied to a wider range of pain types and chronicity than originally suggested. These findings increase the application of the RGS as a pain scale and welfare improvement tool. Abstract : Supplemental Digital Content is Available in the Text.The ability of spontaneous behavioral assays to assess chronic pain is limited. In colitis, RGS identified acute and chronic pain, burrowing identified acute pain.